АСИНХРОННИЙ ЕЛЕКТРОПРИВОД З КЕРУВАННЯМ ЗА РЕАКТИВНОЮ ПОТУЖНІСТЮ - Чепкунов, Р.А. (Інститут електродинаміки НАН України, Київ, 2021)
The method of control of asynchronous electric drive, which based on measuring and control of reactive power of induction motor, is presented. It provides independence of magnetic flow of rotor from changes of induction motor parameters, uninterrupted diapason of regulation of speed including zero and fast regulation. References 7, figures 4.